A case report on the significance of clinical pharmacy services in India. Issue 3 (22nd March 2014) - Dhingra, Sameer; Kumria, Rachna
Key Clinical Message A clinical pharmacist offers invaluable support in the development of a final prescription with better patient management and enhanced safety. Increasingly, medical practice is becoming a team effort with a specialized skill matrix, concentrating on multifaceted support for patient management. A physician undoubtedly leads the team, comprised of a specialist and skilled clinical pharmacist, among others, with skill sets to detect drug interactions, adverse effects, and therapeutic incompatibilities to enable the health‐care team to achieve therapeutic outcomes on a case‐by‐case basis.